2005
DOI: 10.1111/j.1365-2249.2005.02975.x
|View full text |Cite
|
Sign up to set email alerts
|

Natural killer cell activities of synbiotic Lactobacillus casei ssp. casei in conjunction with dextran

Abstract: SummaryWe have reported previously that Lactobacillus casei ssp. casei , together with specific substrate dextran, exhibited an adjuvant effect of stimulating humoral immune responses against bovine serum albumin (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
43
0
3

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(46 citation statements)
references
References 34 publications
0
43
0
3
Order By: Relevance
“…Accordingly, we investigated what kind of beneficial bacteria acting as probiotics could utilize Dex, and found that Lcc could uniquely utilize Dex. Furthermore, the unique and specific combination of Lcc and Dex as a synbiotic had oral immuno-adjuvant activity in mice [13,14] and laying chickens [15]. When Lcc was orally administered with Dex to the mice, Lcc was specifically detected in the intestine and total lactobacilli in the intestinal microflora were significantly increased.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Accordingly, we investigated what kind of beneficial bacteria acting as probiotics could utilize Dex, and found that Lcc could uniquely utilize Dex. Furthermore, the unique and specific combination of Lcc and Dex as a synbiotic had oral immuno-adjuvant activity in mice [13,14] and laying chickens [15]. When Lcc was orally administered with Dex to the mice, Lcc was specifically detected in the intestine and total lactobacilli in the intestinal microflora were significantly increased.…”
mentioning
confidence: 99%
“…It was reported that Lactobacillus casei subsp. casei JCM 1134 T (Lcc) uniquely and specifically utilizes Dex, and that a new synbiotic of Lcc in conjunction with Dex enhances humoral and cell-mediated immune responses in mice [13,14] and chickens [15].…”
mentioning
confidence: 99%
“…Unfortunately, successful synergistic synbiotic combinations are not well established in the literature despite a large number of studies. To our knowledge, only two reports describe a synbiotic combination in which the prebiotic significantly enhanced the stability, persistence, or metabolic activity of a specific probiotic strain in vivo (17)(18)(19). As noted by Kolida and Gibson (16), this low success rate may be explained by the selection of most synbiotic combinations on an arbitrary basis, including shelf life, industrial performance, availability, and cost.…”
mentioning
confidence: 80%
“…This accounts for experiments using synbiotic formulations in humans (61), rats (62,63), and other animal models (64). These findings suggest that, with few exceptions (17)(18)(19), probiotic strains are unable to compete against the resident gut microbiota, which is inherently resistant to outside colonizers (65), even when an exogenous growth substrate in the form of a prebiotic is provided.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation